A case of insulinoma with hypoglycemia that was better managed with lanreotide than octreotide. Issue 5 (19th May 2021) - Yamaoka, Keiko; Nagashima, Shuichi; Okada, Nobukazu; Sawayama, Nagisa; Saito, Shinsuke; Takahashi, Manabu; Okada, Kenta; Endo, Kazuhiro; Koizumi, Masaru; Sasanuma, Hideki; Ebihara, Ken; Kasajima, Atsuko; et al.
Abstract: Long‐acting somatostatin analogs, including lanreotide slow release (LAN‐SR) and octreotide long‐acting release (OCT‐LAR), can improve hypoglycemia in insulinoma. LAN‐SR may be more beneficial in some patients with insulinoma than OCT‐LAR. Abstract : Long‐acting somatostatin analogs, including lanreotide slow release (LAN‐SR) and octreotide long‐acting release (OCT‐LAR), can improve hypoglycemia in insulinoma. LAN‐SR may be more beneficial in some patients with insulinoma than OCT‐LAR.